Matematyka
Konto usunięte
2018-07-11 12:46:37
Oblicz: 2 do -3 razy 4 do -2/ 2-6 wiecej w zalaczniku
Odpowiedź
Apostroff
2018-07-11 15:16:00

[latex]a) = (2^{-3}*2^{-4}):2^{-6}=2^{-7}:2^{-6}=2^{-1}=1/2\b)=(2^{-2}*5^{-2}):(5^{-6}*5^{4})=(2^{-2}*5^{-2}):5^{-2}=2^{-2}=1/4[/latex]

Bastim
2018-07-11 15:17:15

[latex]a) \dfrac{2^{-3}cdot 4^{-2}}{2^{-6}}=dfrac{2^{-3}cdot left ( 2^2 ight )^{-2}}{2^{-6}}=dfrac{2^{-3}cdot 2^{-4}}{2^{-6}}=2^{-3-4+6}=2^{-1}=0,5[/latex] ====================== [latex]b) \dfrac{10^{-2}}{5^{-6}cdot 25^2}=dfrac{2^{-2}cdot 5^{-2}}{5^{-6}cdot left ( 5^2 ight )^2}=dfrac{0,25cdot 5^{-2}}{5^{-6}cdot 5^4}= \\=0,25cdot 5^{-2+6-4}=0,25cdot 5^0=0,25cdot 1=0,25[/latex]

Dodaj swoją odpowiedź